Can global modern slavery be footprinted for corporate due diligence? A data review and analysis. - Reiner, Vivienne; Malik, Arunima; Murray, Joy (Journal of Industrial Ecology, 2025)
Modern slavery laws are increasingly being adopted by countries, requiring companies to demonstrate human rights due diligence. Attempts at quantifying modern slavery across the world have played a crucial role in awareness raising, and locally rich data have been used to provide insights into supply chains for specific sectors and regions but is there a tool that businesses can use wherever they are? We investigate the possibility of developing a universal, global modern‐slavery satellite account for footprinting and as a first step, carry out a comprehensive review of global modern slavery data, estimates, and potential proxies. In addition to data on confirmed cases being unrepresentative of the likely population, estimates risk high sampling errors and low reproducibility. We also analyze data that might be used as "slavery‐like" indicators; however, none could be recommended. Such attempts at footprinting modern‐day slavery are fraught because the identified supply‐chain hotspots resulting from direct expenditure are based on these modern‐slavery datasets that are not fit for such a purpose. Modern‐slavery footprints may be misleading because the complexities and limitations of the data are not well‐represented in a simple indicator, the underlying data are highly uncertain, and the results simply tend to reflect poverty. Although our research highlights that there is no simple way to produce reliable estimates of global modern slavery in supply chains, continued work to build up modern‐slavery data worldwide should support critical, hybrid input–output lifecycle assessment studies, adding to the web of information globally to support ethical decision‐making.